North-South Standards Harmonization and International Trade - Olivier Cadot; Anne-Cécilia Disdier; Lionel Fontagné (Fondation pour les études et recherches sur le développement international (FERDI), 2012)
Recent years have seen a surge in regional trade agreements (RTAs) and the development of non-tariff measures (NTMs). As a consequence, a growing number of RTAs include provisions on NTMs. This paper investigates the effect of standards-harmonization clauses contained in many North-South Agreements on international trade. Using a gravity equation, we find that (i) North-South harmonization of technical regulations reinforces a hub-and-spoke trade structure potentially detrimental to the development of South-South trade and (ii) harmonization on regional standards hurts Southern exports to the North. Thus, standards-harmonization provisions included in many recent North-South RTAs miss their target and contribute to marginalize Southern countries in the worldeconomy.
Keywords: F13; F15; 330